Chemical Standards in Ion Mobility Spectrometry - Fernández-Maestre, Roberto (2010)
In ion mobility spectrometry (IMS), reduced mobility values (K0) are used as a qualitative measure of gas phase ions, and are reported in the literature as absolute values. Unfortunately, these values do not always match those collected in the field. One reason for this discrepancy is that the buffer gas may be contaminated with moisture or other volatile compounds. In this study, the effect of moisture and organic contaminants in the buffer gas on the mobility of IMS standards and analytes was investigated for the first time using IMS directly coupled to mass spectrometry. 2,4-dimethylpyridine, 2,6-di-tert-butyl pyridine (DTBP), and tetrabutylammonium, tetrapropylammonium, tetraethylammonium, and tetramethylammonium chlorides were used as chemical standards. In general, the mobility of IMS standard product ions was not affected by small amounts of contamination while the mobilities of many analytes were affected. In the presence of contaminants in the buffer gas, the mobility of analyte ions is often decreased by forming ion-molecule clusters with the contaminant. To ensure the measurement of accurate reduced mobility values, two IMS standards are required: an instrument and a mobility standard. An instrument standard is not affected by contaminants in the buffer gas, and provides an accurate measurement of the instrumental parameters, such as voltage, drift length, pressure, and temperature. The mobility standard behaves like an analyte ion in that the compound’s mobility is affected by low levels of contamination in the buffer gas. Prudent use of both of these standards can lead to improved measurement of accurate reduced mobility values.